Políticas públicas para integración familiar. - Caiza Orellana, Maritza Carmen (2016)
This academic article, comprises a systematic investigation that aims to determine the construction, implementation and enforcement of public policies established for minors in the period 2010 at 2014, for which the analysis involves the participation of media, who face the crucial task of bringing in the formation of public opinion. The study object comprises content analysis of publications related to the theme of abandonment and child orphanhood, made El Comercio newspaper of Quito daily El Telegráfo of Guayaquil in 2014, this period is specified because much political reforms were made in that year, intending to contrast information around the question ¿How public policies are articulated in abandonment and orphanhood in children? The theoretical basis has been worked, since the contributions of José Sánchez Parga (2004), who exposes his critical arguments and introduces sociology of childhood, then considered the contributions of Wayne Parsons (2007), about the theory and practice the analysis of public policies, which means the origin, construction and possible solution to social problems.